2023
DOI: 10.3390/ijms24032501
|View full text |Cite
|
Sign up to set email alerts
|

Design Hybrid Porous Organic/Inorganic Polymers Containing Polyhedral Oligomeric Silsesquioxane/Pyrene/Anthracene Moieties as a High-Performance Electrode for Supercapacitor

Abstract: We synthesized two hybrid organic–inorganic porous polymers (HPP) through the Heck reaction of 9,10 dibromoanthracene (A-Br2) or 1,3,6,8-tetrabromopyrene (P-Br4)/A-Br2 as co-monomers with octavinylsilsesquioxane (OVS), in order to afford OVS-A HPP and OVS-P-A HPP, respectively. The chemical structures of these two hybrid porous polymers were validated through FTIR and solid-state 13C and 29Si NMR spectroscopy. The thermal stability and porosity of these materials were measured by TGA and N2 adsorption/desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…SCs were developed for the same purpose as secondary batteries and conventional capacitors. They are all used for the convenience of energy storage, but supercapacitors have fewer limitations and wider prospects than the other two [ 26 , 27 , 28 , 29 , 30 ]. For example, its excellent reaction kinetics, higher power density, and gradually improved energy density make it more suitable for charging and discharging [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCs were developed for the same purpose as secondary batteries and conventional capacitors. They are all used for the convenience of energy storage, but supercapacitors have fewer limitations and wider prospects than the other two [ 26 , 27 , 28 , 29 , 30 ]. For example, its excellent reaction kinetics, higher power density, and gradually improved energy density make it more suitable for charging and discharging [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are all used for the convenience of energy storage, but supercapacitors have fewer limitations and wider prospects than the other two [ 26 , 27 , 28 , 29 , 30 ]. For example, its excellent reaction kinetics, higher power density, and gradually improved energy density make it more suitable for charging and discharging [ 26 , 27 , 28 , 29 , 30 ]. In addition, the improved cycle life and wider operating range of SCs allow them to operate stably and continuously [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous organic polymers (POPs), including covalent organic frameworks (COFs), hyper cross-linked polymers (HCPs), and conjugated microporous polymers (CMPs), are promising materials featuring high surface areas and porous properties; they have been used in many applications, including energy storage, iodine (I 2 ) uptake, photocatalysis, catalysis, gas capture/separation, and H 2 evolution. [1][2][3][4][5][6][7][8] For example, Jiang and Tan et al revealed that POPs exhibited the highest capacitance for CO 2 or I 2 uptake. 9, 10 Wang and his group constructed a 3D COF membrane for sieving multi-and monovalent ions.…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors have excellent reversibility, high specific power, stability, and moderate energy density. Electrode material, which can tune the electrochemical activity, is the major component of a supercapacitor. Many organic polymers and metal–organic frameworks (MOFs) have been used as supercapacitor electrode materials. Their excellent electrochemical performance is ascribed to the rapid ion transport and low electrical resistance resulting from their unique structure and surface morphology. , Kuo et al synthesized a covalent triazine organic framework based on the anthracene moiety as a supercapacitor electrode with a specific capacitance ( C sc ) of 589 F/g and a high stability of 95% after 5000 cycles . A nickel-based MOF microflower, reported by Kaneti et al, exhibited a C sc of 1093 F/g at 1 A/g with a high rate capability .…”
Section: Introductionmentioning
confidence: 99%